The Effect Of Milling Time, Stirring Speed And Ball Mill To Powder Ratio Of Malaysian Tin Ore - Kamaruddin, Nur Izaani Akma (Universiti Sains Malaysia, 2018)
In this study, “The Effect of Milling Time, Stirring Speed and Ball Mill to Powder Ratio of Malaysian Tin Ore” has been carried out to characterize raw material and milled product of the tin ore sing XRD, XRF and SEM-EDX. Prior to experimental work, raw material and milled product was characterized using XRD, XRF and SEM-EDX.